Comparison of ultrafiltration and microdialysis for ceftriaxone protein-binding determination. (26th November 2022) - Sanz-Codina, Maria; Wicha, Sebastian G; Wulkersdorfer, Beatrix; Al Jalali, Valentin; Van Os, Wisse; Vossen, Matthias G; Bauer, Martin; Lackner, Edith; Dorn, Christoph; Zeitlinger, Markus
Abstract: Background: High protein binding (PB) of antibiotics has an impact on their antimicrobial activity. It has been questioned whether in vitro PB determination can capture the dynamic and concentration-dependent PB of highly bound antibiotics. Objectives: This clinical study compared in vitro ultrafiltration (UF) and in vivo IV microdialysis (MD) methods to determine ceftriaxone PB. Methods: Six healthy male volunteers received a single IV 2 g dose of ceftriaxone. Unbound ceftriaxone plasma concentrations were measured with MD and venous plasma sampling with subsequent UF. Pharmacokinetic parameters were determined using non-compartmental pharmacokinetic analysis. Non-linear mixed-effects modelling was used to quantify the PB. The PTA was estimated. Results: The C max of ceftriaxone total plasma concentration (297.42 ± 21.0 mg/L) was approximately 5.5-fold higher than for free concentrations obtained with UF (52.83 ± 5.07 mg/L), and only 3.5-fold higher than for free concentrations obtained with MD (81.37 ± 26.93 mg/L). Non-linear, saturable PB binding was confirmed for both UF and MD. Significantly different dissociation constants (Kd ) for the albumin/ceftriaxone complex were quantified: in UF it was 23.7 mg/L (95% CI 21.3–26.2) versus 15.9 mg/L (95% CI 13.6–18.6) in MD. Moreover, the estimated number of binding sites (95% CI) per albumin molecule was 0.916 (0.86–0.97) in UF versus 0.548 in MD (0.51–0.59). The PTA obtained with MD was at most 27% higher than with UF. Conclusions: In vitro UF versus in vivo intravasal MD revealed significantly different PB, especially during the distribution phase. The method of PB determination could have an impact on the breakpoint determination and dose optimisation of antibiotics.